Shared book reading to promote mental well-being among young people with and without Down syndrome: a pilot dyadic randomized controlled trial - Huang, Xiaoyi; Long, Iman; Zhang, Wenjie; Xu, Jikun; Smith, Robert David (Frontiers in Public Health, 2025)
BackgroundWith societal progress and a deepening understanding of Down syndrome (DS), research focus has shifted toward improving the quality of life and education for youth with DS. This study aims to determine the feasibility and estimate the preliminary effectiveness of a dyadic shared book reading program on the health-related quality of life of youth with DS (primary outcome), the mental wellbeing of university students (secondary outcome), and actor–partner outcomes to inform a future definitive trial.MethodsThis study is an 8-week pilot dyadic randomized controlled trial (RCT) comparing a shared book reading intervention to a minimal activity control. The study will then continue for 12 months as a single-arm cohort study. Young people with DS and university students will be recruited, formed into dyads, and then randomized to either the intervention or control group. The intervention involves pairing a young person with DS with a university student for a weekly, 1-h shared book reading session. The control group will be provided with three books to read at their leisure over the 8 weeks. The primary outcome is the health-related quality of life of young people with DS, measured using the Pediatric Quality of Life Inventory (PedsQL 4.0). Secondary outcomes include the Engagement, Perseverance, Optimism, Connectedness, and Happiness (EPOCH) scale for measuring wellbeing. The Friendship Quality Questionnaire (FQQ) will be used to measure the dyad's level of friendship in the intervention group at 8 weeks. Measurements will be taken at baseline (T0) and at 8 weeks (T1). After 8 weeks, all participants will be offered the opportunity to continue in the study, joining the weekly shared book reading intervention; outcome measures will then be assessed at 6-month (T2) and 12-month (T3) follow-ups. Mixed linear regression models will be used to compare the intervention and control groups at 8 weeks. For the 6-month and 12-month follow-ups, change scores from baseline will be analyzed to test for potential long-term effect.DiscussionThis study focuses on the mental wellbeing of young people with DS and university students by promoting psychological health through shared book reading activities.Anticipated resultsIt is expected that the shared book reading activities will improve the mental wellbeing of both young people with DS and university students; however, due to the pilot study's sample size, this trial may not detect effectiveness at a level of statistical significance.Clinical Trial RegistrationClinicaltrials.gov, identifier NCT06813625.